Influence of herbicide Granstar Pro 75, w.g., in vitro conditions on the seed growth of Amarantus retroflexus L. - I. Storchous (Карантин і захист рослин)
Goal. Investigate the herbistatic properties of the herbicide Granstar Pro 75, w.g., regarding its effect on the germination of Amaranthus retroflexus L. seeds, to ensure targeted and rational use in wheat crops, with maximum preservation of the crop and minimal environmental impact.